Engineering in genomics the emerging in-silico scientist; how text-based bioinformatics is bridging biology and artificial intelligence. - Garner, H. (IEEE Engineering in medicine and biology magazine)
Current work in text-based bioinformatics has both immediate and future applications. It has been said that AI has not lived up to its promise, in part because AI is most successful at performing tasks that humans perform poorly and least successful at tasks where humans excel. That is, they excel at tasks such as classification and recognition, but have not been successful in employing methods of logic and reason-the traits we most closely associate with human intelligence. Perhaps AI needs to meet the grand challenges of biomedicine before it can be truly appreciated.